HISTORICAL REVIEW OF RELIGIOUS MALAY MANUSCRIPT WRITINGS BEFORE 1800 - Norhasnira Ibrahim,; Zainora Daud,; Shumsudin Yabi, (Journal of Islamic, Social, Economics and Development, 2022)
The arrival of Islam to the Malay Archipelago is the core reason for the existence of the Jawi script. By using the Jawi script, the expansion of religious Malay manuscripts or Malay-Islamic Kitab writings began to bloom and was estimated in the 12th century. Objectives of this study are (i) to study a brief history of religious Malay manuscript writings before the year 1800, and (ii) to identify Malay authors and their religious Malay manuscript writings based on time-frame production. This article is presented by using qualitative methodology by gathering data from books, journal articles, paperwork, and websites. The result of this study shows that there are two phases of religious Malay manuscript writing which are the first phase is ‘The Translation Phase’ from the 12th to 16th century, and the second phase is ‘The Individual Writing Phase’ from the 17th to 18th century.